Fabrication of zirconia-kaolin dual layer hollow fiber membrane: Physical and performance study for industrial wastewater treatment. (June 2021) - Pauzan, Mohammad Arif Budiman; Othman, Mohd Hafiz Dzarfan; Ismail, Nurul Jannah; Puteh, Mohd Hafiz; Ismail, Ahmad Fauzi; A. Rahman, Mukhlis; Jaafar, Juhana
Abstract: This work aims to prepare a robust yet low-cost dual-layer hollow fibre ceramic membrane composite membrane (DLZK) fabricated by co-extrusion phase inversion/co-sintering technique to be used in wastewater treatment. The dope suspensions were extruded simultaneously where the outer layer consists of zirconia while the inner layer consists of a mixture of kaolin and zirconia to enhance membrane performance in terms of mechanical strength and wastewater treatment capability. The effects of co-sintering temperature from 1200 to 1500 °C on the membrane's mechanical strength, porosity, pore size, water permeability, and dissolubility in high alkaline/pH condition were investigated. The membrane performance was evaluated by real wastewater treatment test using two different types of industrial wastewaters which are palm oil mill effluent and textile industry wastewater. The findings show that the proposed method of producing the DLZK membranes could provide good interfacial adhesion and well-dispersed zirconia in the outer layer and the use of kaolin as an alternative natural material for ceramic membrane fabrication. The DLZK co-sintered at 1200 °C had the mechanical strength of 65 MPa, only 3.5 % loss of the original shape in high alkaline solution, and removed almost 95 % for all parameters of COD, TOC, TN, NH3 -N and TSS in the both wastewaters suitable for microfiltration purpose.